INFLUENCE OF SYMBOLS OF A FOLK ART OF UKRAINE ON FORMATION OF FIGURATIVE THINKING IN THE FINE ARTS (Pedagogy of Higher and Secondary Education, 2022)
The artical gives the investigetion of simbols of folk art, the iconographie art pecific, synonymical names and contents, and also gives and also the influence of simbols on the fluid in graphic art.